353 Comparison of Ocular Outcomes in Pediatric Posterior Fossa Tumors. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Gadgil, Nisha; Stormes, Katie; Shah, Veeral; Lam, Sandi
Abstract: INTRODUCTION: Ophthalmological symptoms and abnormalities are common amongst pediatric patients with posterior fossa tumors, which may be a result of disruption of ocular afferent and efferent systems either due to tumor or as a result of surgery. The ophthalmic complications and outcomes associated with the management and treatment of these tumors have received little attention in the literature. METHODS: We did a retrospective analysis of patients who underwent index surgery for resection of posterior fossa tumor from 2007 to 2016 at a tertiary free-standing academic pediatric hospital. Descriptive statistics, univariate and multivariate regression were performed to assess the risk of ophthalmologic sequelae. RESULTS: A total of 182 patients who had undergone posterior fossa craniotomy for neoplasm were included in the study. Ophthalmologic symptoms were the fourth most common presenting complaint, and initial ophthalmologic exam was abnormal in 40% of patients. Evaluation of visual acuity demonstrated a good outcome in 88% of patients following treatment. The most common postoperative oculomotor finding was esotropia (29%) which resolved spontaneously in more than half of patients. A good outcome was obtained in all patients requiring surgery for esotropia. Hypertropia due to trochlear nerve palsy was noted in 14% of the cohort and less than half resolved spontaneously. Of those requiring strabismus surgery for hypertropia, less than half had a good outcome. Multivariate analysis confirmed the correlation between cerebellar mutism and postoperative esotropia and hypertropia. Clinically significant nystagmus was seen in 8% of the cohort, which may impede vision even when acuity is normal. CONCLUSION: It is imperative to allow for the best possible vision to survivors of posterior fossa tumors, as many of the sequelae are treatable. Our results indicate a good visual outcome in the majority of pediatric patients undergoing resection of posterior fossa tumors if ophthalmologic complications are vigilantly assessed and treated.